Analyzing and modeling an urbanizing tropical watershed for sustainable land use planning - Memarian, Hadi Khalil Abad (2012)
Land use changes in river basins result in flooding events that increase sediment load, which is a global concern and is becoming one of the main land management issues. Urban and agriculture development contributes to increasing trend of environmental damage within the Langat River Basin. Thus, an optimum land use pattern is necessary to meet long-term sustainable development in and around the basin. Recently, the geographic information system-based spatial process modelling have become indispensable tools for understanding natural processes occurring at the watershed scale. This study was concentrated on an applied framework for land use planning within the Langat upper catchments using the most applicable approaches for trend analysis, land use and hydrological modelling, and goal programming. In this study, the proposed framework for land use planning involved four main steps, i.e. hydrological trend analysis, land use modelling, landscape assessment and scenario making, hydrological modelling, and goal programming. Non-parametric tests, i.e. Mann-Kendall and Pettitt were used to detect gradual and abrupt changes in the hydrological data sets. The ‘Cellular Automata-Markov’ (CA-Markov) approach was utilised to simulate the land use change for 2020. Landscape analysis was performed using Patch Analyst to calculate six fundamental landscape metrics. Hydrological analysis was done using the ‘Kinematic Runoff and Soil Erosion,Version 2’ (KINEROS2) as an event-based model and ‘Soil and Water Assessment Tool’ (SWAT) as a continuous simulation model. Weighted goal programming (WGP) integrated with analytic hierarchy process (AHP) was employed to define optimum land use scenarios. Trend analysis results indicated significant upward trend in water discharge and increasing tendency in sediment load at the Hulu Langat Sub Basin. These increasing trends were mainly caused by rapid changes in land use. Therefore, the Hulu Langat sub basin was introduced as the most critical sub basin,in terms of hydrological changes. Validation results of CA-Markov showed a weak robustness for land use and cover change simulation due to uncertainties in the source data, the model, and future land use and cover change processes in the study area. The future land use map simulated by CA-Markov was not applied in SWAT application. However, due to capability of SWAT in land use updating, the land use map dated 2006 was updated using a transition probability matrix computed by the Markov chain. Calibration results of KINEROS2 showed excellent and very good fittings for runoff and sediment simulations based on the aggregated measure. Validation results demonstrated that KINEROS2 was reliable for runoff modelling while KINEROS2 application for sediment simulation was only valid for the period 1984-1997. Land use and cover change impacts analysis by KINEROS2 revealed that direct runoff and sediment discharge increased with the progress of urban development and unmanaged agricultural activities. The SWAT robustness for water discharge simulation during the period 1997-2008 was good. However, due to uncertainties in the conceptual model, its robustness for sediment load simulation was only acceptable for the validation period of 2002-2004. SWAT simulation based on the future scenario caused 2.37% and 25.59% increase in monthly direct runoff and monthly sediment load, respectively, as compared to the baseline scenario. Hydrological simulation based on the water conservation scenario resulted in 2.76% and 27.48% relative decrease in monthly direct runoff and monthly sediment load,respectively, as compared to the baseline scenario. In land use optimisation, four planning alternatives were defined, i.e. A1, A2, B1, and B2. The deriving factors in land use optimisation using goal programming were: (1) Water yield, (2) Sediment load, (3) Biomass yield, (4) Surface runoff, and (5) Net income. The alternatives A1 and A2 were formulated to optimise the baseline scenario in order to achieve a possible level of water conservation targets and yield a moderate level of transition cost, with and without limitation in horticulture/cropping activities, respectively. The alternatives B1 and B2 were formulated using the same concept, but with some constraints aimed at transforming the baseline scenario toward the future plan. The analytic hierarchy process integrated with weighted goal programming approach resulted in four optimised land development alternatives that can be applied within the Hulu Langat Sub Basin.